Growth of indium oxide based nanostructures by plasma assisted reactive thermal evaporation for photoelectrochemical application / Azianty Saroni - Azianty , Saroni (2018)
In this work, indium oxide based nanostructures were grown in a home-built system using plasma assisted reactive thermal evaporation (PARTE) followed by nitrogen plasma assisted in-situ thermal annealing. The main concern of this work is to grow various types of indium oxide based nanostructures for photoelectrochemical (PEC) water splitting application using this technique. The first part of experiment is focused on the growth of In2O3 composite nanostructures by nitrogen plasma assisted in-situ thermal annealing at filament temperatures (Tf ) varies from 1300 to 1800 °C and with the radio frequency (rf) power fixed at 50 and 150 W. The in-situ thermal annealing transformed the composition of the composite nanostructures from In2O3/InN to In2O3/WO3 and In2O3/W2N with increase in Tf at both rf power. High Tf, has the effect of transforming the morphology of the nanostructures from spherical-shaped grains of In2O3/InN composite nanostructures to rhomboidal shaped grains with significant crystal facets of In2O3/W2N. The research revealed that there was an obvious reduction of crystallite size when the rf power was increased. Consequently, this also resulted in tailoring of the optical energy gap (